2024
DOI: 10.3389/fvets.2024.1359213
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combining green iron nanoparticles and algae on the sustainability of broiler production under heat stress conditions

Yousri A. R. Almeldin,
Amira E. Eldlebshany,
Enass Abd Elkhalek
et al.

Abstract: BackgroundNatural feed additives in broiler feed contribute to the overall health, productivity, and economic viability of broiler chickens while meeting consumer demands and preferences for natural products. The purpose of this research was to determine the effect of green iron nanoparticles (Nano-Fe) and Halimeda opuntia supplementation in broiler diets on performance, ammonia excretion in excreta, Fe retention in tissues and serum, carcass criteria, and meat quality under hot environmental conditions.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Its enhanced bioavailability, targeted delivery, and reduced environmental impact make it an attractive option for poultry producers seeking to optimize broiler performance while promoting sustainability. In our prior investigation, it was demonstrated that incorporating green Nano-Fe into broiler diets, either with Halimeda opuntia as a carrier or independently, has the potential to enhance broiler performance and health, particularly in hot environmental conditions ( 16 ). There is still much to learn about the long-term effects, optimal dosage, and specific mechanisms of action of Nano-Fe in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Its enhanced bioavailability, targeted delivery, and reduced environmental impact make it an attractive option for poultry producers seeking to optimize broiler performance while promoting sustainability. In our prior investigation, it was demonstrated that incorporating green Nano-Fe into broiler diets, either with Halimeda opuntia as a carrier or independently, has the potential to enhance broiler performance and health, particularly in hot environmental conditions ( 16 ). There is still much to learn about the long-term effects, optimal dosage, and specific mechanisms of action of Nano-Fe in poultry.…”
Section: Introductionmentioning
confidence: 99%